The interpretive work of Efraín Loyola: a reference in Cuban flute playing within the charanga orchestra (Islas, 2022)
ABSTRACT: Introduction: The objective of this article is to assess the significance of Efraín Loyola's interpretive work within the charanga orchestra. Methods: It is a prescriptive, descriptive analysis based on John Rink's model. This theory encompasses the formal and conceptual analysis of music itself and the interpretative contributions of the performer's subjectivity. Results: It is noticeable the use of positions not contemplated in the traditional methods of flute teaching to obtain homonymous sounds in the different registers. The preference of the wooden flute with five keys on the system flute stands out, giving the interpretation a more accentuated and less strident sound. This makes Efraín Loyola's interpretative work stylistically recognizable as it possesses a personal and distinctive expressiveness. Conclusions: The contribution of Efraín Loyola, first as part in the Aragón orchestra and the later brass bands founded by him, ranges from the particular choice of the instrument, to new positions for its execution, not contemplated for the flute in the traditional teaching methods or in the studies consulted.
Keywords: charanga orchestra; flute; interpretativa work; Efraín Loyola